A Blended Learning Approach for Educating Software Project Management - Radaideh, Moh’d A.; Al-Haija , Qasem Abu (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Aim: A prevalent field of study within Software engineering (SE), software project management (SPM) has attracted an increasing percentage of scholars and professionals in recent years. It is a component of project management where software projects are designed, carried out, monitored, and administered. This article explores the author’s strategy for delivering an SPM course in an integrated online format. By January 2020, the course above will have been reorganized into three modules, including a new one on Agile/Scrum project management, and transformed into a blended online course. The novelty and contribution of this work can be depicted from the status of the "SE440 SPM" course as the first academic senior SPM course to be delivered as a blended online one. At the same time, it incorporates four views of SPM: the author’s view, the PMI’s approach, the IEEE-CS perspective, and the SCRUM SPM approach. In addition, it sought to identify the optimal course contents and delivery method and define a set of instruments that could be used to facilitate the accepted delivery method. Throughout its extensive revisions, the course adheres to the Institute of Engineering and Technology (IET) and Accreditation Board for Engineering and Technology (ABET) accreditation standards.